Betamethasone-exposed preterm birth does not impair insulin action in adult sheep. Issue 2 (February 2017) - De Matteo, R; Hodgson, D J; Bianco-Miotto, T; Nguyen, V; Owens, J A; Harding, R; Allison, B J; Polglase, G; Black, M J; Gatford, K L
Abstract : Preterm birth is associated with increased risk of type 2 diabetes (T2D) in adulthood; however, the underlying mechanisms are poorly understood. We therefore investigated the effect of preterm birth at ~0.9 of term after antenatal maternal betamethasone on insulin sensitivity, secretion and key determinants in adulthood, in a clinically relevant animal model. Glucose tolerance and insulin secretion (intravenous glucose tolerance test) and whole-body insulin sensitivity (hyperinsulinaemic euglycaemic clamp) were measured and tissue collected in young adult sheep (14 months old) after epostane-induced preterm (9M, 7F) or term delivery (11M, 6F). Glucose tolerance and disposition, insulin secretion, β-cell mass and insulin sensitivity did not differ between term and preterm sheep. Hepatic PRKAG2 expression was greater in preterm than in term males ( P  = 0.028), but did not differ between preterm and term females. In skeletal muscle, SLC2A4 ( P  = 0.019), PRKAA2 ( P  = 0.021) and PRKAG2 ( P  = 0.049) expression was greater in preterm than in term overall and in males, while INSR ( P  = 0.047) and AKT2 ( P  = 0.043) expression was greater in preterm than in term males only. Hepatic PRKAG2 expression correlated positively with whole-body insulin sensitivity in males only. Thus, preterm birth at 0.9 of term after betamethasone does not impair insulin sensitivity or secretion in adult sheep, and has sex-specific effects on gene expression of the insulin signalling pathway. Hence, the increased risk of T2D in preterm humans may be due to factors that initiate preterm delivery or in early neonatal exposures, rather than preterm birth per se .